Bloqueio peribulbar com ropivacaína a 1% guiado por ultrassonografia em cães: avaliação e padronização da técnica - Wagatsuma, Juliana Tessália [UNESP] (2013)
he regional blocks are used in veterinary medicine as part of a balanced anesthesia protocol, next to inhalational anesthesia. The effectiveness, however, is variable front due to the difficulty of achieving anatomical references vague or inexperience of the performer. The peribulbar has indicated for ophthalmic procedures in general, but the technique requires care by the proximity of the needle to the eyeball that if an error occurs, can lead to perforation of the same. The monitoring with ultrasound image may be a great tool in the implementation of local techniques, especially the delicate and access-threatening injuries as peribulbar block. Aiming to standardize the technique of peribulbar guided by ultrasound in dogs, this work was performed with the following: in the first phase, four dogs euthanized recently underwent peribulbar injection guided by ultrasound with the administration of methylene blue 1% for identification of the structures affected by ocular and orbital solution. The second phase occurred in the form of comparative study of the duration of sensory block, motor and ophthalmic complications observed during the assessment of the conventional peribulbar and ultrasound-guided technique with 1% ropivacaine in 15 healthy dogs. The results showed akinesia, motor and sensory block equivalents, with the occurrence and severity of ophthalmic complications similar, except the conjunctival haemorrhage had major repercussions in the way traditional bulbs blocked. It was concluded that the standardization of the peribulbar technique with lower single puncture guided by ultrasound has applicability in dogs, with the advantage of promoting visual confirmation of the accuracy of the technique and the correct deposition of the anesthetic agent in the proper place, concomitantly the preservation of eye structures, with satisfactory quality and duration